KECANDUAN GAME ONLINE DAN POLA ASUH ORANG TUA DI KALANGAN SISWA MTS AL- MUTTAQIN PEKANBARU - Dina Zakiyah; Rosmawati Rosmawati; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The phenomena in school today, both in public schools and private schools, are many children who fill their free time by playing online games, playing online games at this time not only as filling in the blanks but also neglecting one's work both online game play as well can make people addicted and have an adverse impact on him. The purpose of this study is: To find out the description of online game addiction and parenting parents among students of MTS Al-Muttaqin Pekanbaru. This research was carried out by taking the location at MTS Al Muttaqin Pekanbaru which is located at Jalan HR. Soebrantas KM. 13.5, Kecamatan Tampan Pekanbaru. Research time in May 2018 in the 2017/2018 school year. The research method used in this research is quantitative descriptive method. The population in this study amounted to 74 students. The study sample was 44 students. Based on the results of the research conducted, it can be concluded that: online gaming addiction among Al-Muttaqin Pekanbaru MTS students in terms of all the highest aspects is in the Withdrawal indicator and the lowest aspect is Interpersonal and health-related problems. The highest parenting style among students of MTS Al-Muttaqin Pekanbaru is democratic parenting. The meaning of democratic parenting is most dominantly applied followed by authoritarian and permissive parenting.Keywords: online game addiction, parenting.